Manipulative Learning Accommodates Fraction Comprehension In Inclusive Elementary Classrooms: Pembelajaran Manipulatif Mengakomodasi Pemahaman Pecahan Di Ruang Kelas Dasar Inklusif - Musdalifah Musdalifah; Siti Rohmah Nurhayati (Academia Open, 2026)
General Background Mathematics education requires logical reasoning, where fractions represent a notoriously difficult transition from whole-number concepts to proportional thinking. Specific Background Within inclusive elementary environments, traditional teacher-centered instruction frequently fails to provide concrete learning experiences, leaving regular learners alongside students with dyscalculia or slow learning traits struggling to interpret abstract numerical representations. Knowledge Gap Although physical learning tools are widely researched in homogeneous settings, empirical evidence detailing their systematic application to simultaneously support neurotypical children and those with special educational needs in a single space remains scarce. Aims This Classroom Action Research investigates the application of concrete instructional materials, guided by Bruner’s cognitive representation stages, to advance mathematical understanding among twenty-three diverse fourth-grade students at SD Negeri 017 Sangatta Utara. Results The intervention significantly raised classical conceptual mastery from a 26.09% pre-action baseline to 86.96% by the conclusion of the second cycle. Furthermore, the students' average test scores increased substantially from 55.21 to 77.26. Novelty This study uniquely validates that transitioning sequentially through enactive, iconic, and symbolic representations using tangible objects successfully bridges the cognitive demands of abstract mathematics for highly diverse learner profiles simultaneously. Implications Educators must adopt hands-on pedagogical strategies to provide equitable, concrete learning scaffolds that accommodate individualized cognitive requirements during complex arithmetic instruction. Highlights Utilizing concrete instructional materials successfully bridges abstract mathematical gaps for slow learners and dyscalculic students. Conceptual mastery of proportional mathematics surged from a 26.09% baseline to an 86.96% final achievement rate. Transitioning sequentially through distinct cognitive stages minimizes cognitive overload during complex arithmetic instruction. Keywords Inclusive Education; Manipulative Instruction; Fraction Comprehension; Cognitive Representation; Classroom Action Research